Diagnostic Challenges in Sports Cardiology - Malek, Lukasz; Postuła, Marek (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
The foundations of sports cardiology include promoting physical activity and providing a safe environment for training and competition for all athletes at all levels, from professional to recreational. To combine these two aims, reliable tools to perform preparticipation screenings are needed. Moreover, those at high risk of potentially life-threatening events should be advised to limit their training load, while others should be reassured that there is no exercise-related cardiovascular risk. We are currently witnessing the advent of new portable devices for remote and mobile heart monitoring and several new and promising biochemical markers, which can support athletes' diagnostic processes. In this Special Issue of the Diagnostics journal entitled "Diagnostic Challenges in Sports Cardiology", we present a series of 13 manuscripts, including eight original works, three reviews, and two case reports, which give a glimpse into the current research topics in the area of sports cardiology.